Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Mobil Merek Nissan: Studi pada Konsumen PT Wahana Wirawan Indomobil Plaza Aceh - Teuku, Fadhlul; Erlinda Erlinda; Sulfitra Sulfitra (Jurnal Sains dan Ilmu Terapan, 2025)
This study aims to examine the effect of price and product quality on purchasing decisions at PT. Wahana Wirawan Indomobil Plaza Aceh. The data collection technique uses a questionnaire. The method used is the associative method which aims to determine the magnitude of the influence of the independent variables (price and product quality) on the dependent variable (purchase decisions) partially and simultaneously. Determination of the sample using the census technique. The sample used in this study amounted to 98 consumers of PT. Wahana Wirawan Indomobil Plaza Aceh and were willing to be respondents. The results of the study indicate that price partially influences the purchasing decision of PT. Wahana Wirawan Indomobil Plaza Aceh and product quality partially influences the purchasing decision of PT. Wahana Wirawan Indomobil Plaza Aceh.